Pemilihan Alternatif Strategi Bisnis Pada Line Bisnis Merchandise di PT. Caladi Lima Sembilan (C-59) Bandung - Jawa Barat - Dini Yulianti (Universitas Insan Cendekia Mandiri, 2022)
: The business line at the C59 company consists of four, namely international, retail, order, and merchandise. In the line of merchandise business, there is a problem with this business. Namely that the sales target that has been set by the company has never been achieved, while the business opportunity is still wide. As a first step, identification of the company's external and internal business data is carried out. There are five problem-solving models used for data processing, namely the SAP and ETOP systematic approaches to critically identify external and internal factors, the IFE and EFE matrices, which are Input Stages that function to evaluate external and internal evaluation factors, while for the Matching Stage, only two matrices are used, namely the IE matrix to position the SBU in a 9-cell matrix, and the SWOT matrix to formulate the company's strategy, while the QSPM, which is the Decision Stage, functions to choose the The results of the IFE and EFE matrices are (2.66; 2.55) so that the position of the SBU in the IE matrix is in cell V, which results in a hold and maintain strategy. The general strategies used are market penetration strategy and product development strategy. The SWOT matrix produces nine alternative strategy formulations. At the Decision Stage, QSPM uses an alternative strategy from the IE matrix, because it is considered that nine alternative strategies from the SWOT matrix have been reflected in the hold and maintain strategy. So, the results of QSPM data processing produce Sum TAS 6.63 for market penetration strategy and 5.15 for Sum TAS product development strategy. So the market penetration strategy was chosen as the right strategy for the C59 merchandise business line. The market penetration strategy planning program is made in the form of action plans and gantt charts, namely providing examples of merchandise products, giving discounts and competitive product prices, helping with the cost of printing campus/school bulletins by installing a logo, participating in campus events, and sponsoring school/campus activities.